Defect Closure After Wide Excision of Basal Cell Carcinoma : A Case Series - Febriakhano, Aji; Rahmani, Salsabila; Pangestu, Wahyuning; Andadari, Ammara Rona; Wahyuni, Wira (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2025)
Basal cell carcinoma is the foremost common skin cancer, accounting for 75-80% of nonmelanoma cancers. This malignancy is commonly found in sun-exposed areas like the face and neck. This malignancy rarely causes death, but it can result in significant local damage to the soft tissue, cartilage, and bone, impacting both function and aesthetics, particularly in the facial region. The main treatment for BCC is wide excision followed by reconstruction to close the defect. The choice of reconstructive procedure depends on various factors, such as size, location, involvement of deeper structures, cosmetic considerations, and function. There are various types of facial skin reconstruction, including local and regional flaps. This case series reports reconstruction of basal cell carcinoma after wide excision using local and regional flaps. Local and regional flaps provide matching skin color and texture as well as adequate blood supply. Both have superior aesthetic and functional advantages.